COVID-19 serological evaluation in a cohort of Vaccinated and Seropositive healthcare workers - D'Amato, Smeralda; Squeri, Raffaele; La Fauci, Vincenza; Pantò, Giuseppe; Esposito, Ennrica Maria; Denaro, Federica; Visalli, Giovanna; Giunta, Ioselita; Venuto , Roberto; Privitera, Antonino; D'Urso, Lorenzo; Cortese, Rosaria; et al. (Acta Biomedica Atenei Parmensis, 2021)
Introduction: Severe Acquired Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2) infection represents an unprecedented public health problem and, at present, vaccination is the only weapon available to combat the infection. The simplest and most immediate method to quantify the response of the subject's immune system to vaccination and / or infection is the serological assessment of the antibody titer. The objective of our study was 1) to evaluate the presence of antibody responses in a sample of healthcare workers subjected to a complete vaccination course as per ministerial provisions (double dose for negatives and single dose for ex-SARS-CoV subjects -2 positive) with Comirnaty vaccine (Pfizer / BioNTech) 2) evaluate the presence of statistically significant associations for sex, age and previous positive swab. Materials and methods: the antibody levels of both nucleocapsid antibodies and anti-Sars-CoV2 Spike antibodies of the study subjects were examined with the electrochemiluminescent immunoassay (ECLIA) method developed by Roche®. The cut-off value, as suggested by the manufacturer, for anti-nucleocapsid antibodies was 1 COI, while the Ig Spike value was 0.8 I / mL. The study sample was stratified by age (≤45 years, 46-55, ≥56 years old), previous positive molecular swab, gender and IgG S1 / S2 values ​​at the completed vaccination course (≤200, ≥200 AU / mL ). Statistical analyzes were carried out with the R software. Results: almost all of the sample (89.45%) showed IgG Spike values> 200 AU / mL with statistically significant associations in relation to sex (greater in females, p≤0.05), to previous swab positivity in the presence of a vaccine dose (n = 44; p